PERFORMANCE EVALUATION OF FLOW THROUGH TRIANGULAR WEIRS WITH BOTTOM ORIFICES - Hamza, Isah; Muhammad, Muhammad Mujahid; Otun, Johnson; Jen, Terhile Thaddeus; Umar, Zacchaeus Simpa (FUDMA JOURNAL OF SCIENCES, 2022)
This study attempted to evaluate the performance capacity of Triangular weirs with bottom orifices by varying the crest angles, diameters and number of orifices. Forty- Eight (48) triangular weirs with bottom orifices with crest angles of degrees 450, 600, and 900 with varying orifice sizes of diameters 6.5 mm, 7.5 mm and 8.5 mm and the number of orifices ranging from one to five. The analysis of the results indicates that, the discharge (Q) increases with an increase in effective head above crest (Ha) while the discharge coefficients (Cd) are found increasing steadily as the number of orifices and diameter increases with a minimum and maximum Cd of 0.3128 and 1.7986 respectively while the hydraulic performance of the models increasing as the number of orifices increases with the best hydraulic performance of the weirs determined to be 1.7630 at the model of angle 900 with five orifices of diameter 8.5 mm